Study and Implementation of Internet of Things (IoT) Based Vehicle Safety Alert and Tracking System - Sarasvathi, Nahalingham; Fong, Jason Zu XiN (INTI International University, 2018)
The project studies and implement Internet of Things (IoT) technology into the current vehicle system, with sided towards the safety portion of the aspects. With the problems of today’s postaccident death due to loneliness in the event of accident, and huge monetary loses from stolen vehicle has inspired the author to test out the idea to mitigate them. The purpose of this project is to able to ultimately provide safety alert system such as accident and vehicle theft alert without human intervention throughout the process. Moreover, this system shall be able to also let user locate the vehicle also known as the prototype in this project. This will be achieved by integrating IoT technology with microcontroller, embedded sensors along with the use of Open Source materials, platforms, and Cloud services. The author will be utilizing a GUI interface to allow the monitoring of the prototype. The proposed system is able to avoid extra costs gone to waste in case of a hijacking event and also in some cases help to save lives from succumbing by the power of after crashes.